What factors affect the recurrence of gastritis in adolescents: A case study of students at State Senior High School 1 Surade - Saepul Alamsah, Mustopa; Safariyah, Erna; Danismaya, Irawan; Hamzah, Amir (Science Midwifery, 2024)
Gastritis is very disruptive to daily activities, so it can result in decreased quality of life, and less productive. If gastritis is not treated properly, it will have an impact on the patient. Preventing gastritis should be done by reducing the factors that influence the occurrence of the disease. The purpose of this study was to determine the factors that influence gastritis recurrence in adolescents at SMAN I Surade. As for the type of research used is correlation descriptive observation. This study uses total sampling technique. The sample used in this study amounted to 40 adolescents who had gastritis or ulcer pain. This study used a questionnaire. The analysis method used is statistical test using Chi Squere. The results showed that there was a relationship between dietary factors with the frequency of gastritis recurrence of 0.035 <0.05, with a closeness of 0.453 in the moderate category. There is a relationship between stress factors with the frequency of gastritis recurrence of 0.021 <0.05, with a closeness of 0.473 in the moderate category. There is a relationship between dietary factors with the frequency of gastritis recurrence of 0.002 <0.05, with a tightness of 0.483 in the moderate category with the most influential factor on gastritis recurrence is the drug consumption factor.